O sensível da imagem: sensorialidade, corpo e narrativa no cinema contemporâneo da Ásia - Silva, Camila Vieira da (2010)
Introducing as a theme the relation between sensoriality, body and narrative at the recent cinema production released in Asian countries, as Thai, Taiwan and Japan, this paper searches to investigate how movies as Tropical Malady (Sud Pralad, 2004), by Apichatpong Weerasethakul; Goodbye, Dragon Inn (Bu San, 2003), by Tsai Ming-Liang; Café Lumière (Kôhî Jikô, 2004), by Hou Hsiao-Hsien; e Shara (Sharasojyu, 2003), by Naomi Kawase, are related to an understanding of an specific form of cinema, based in questions about the sensorial and the body, which also implies at a kind of narrative construction audiovisual. This hypothesis is that such contemporary filmmakers brings at their movies a kind of attention to everything that is related at pathos (affections, feelings) and the conservation of human anthropological integrity. Released at the market of international film festivals between 2003 e 2004, these four feature films were chosen as object of study, based at the hypothesis that are in them an specific kind of image, which privileges sensorial aspects that interfere directly on narrative construction.